Coral communities of San Juan del Sur, Pacific Nicaragua - Alvarado Barrientos, Juan José (2011)
There are few environments conducive to coral growth along the Pacific coast of Nicaragua, due mostly to strong upwelling toward the south and the lack of adequate substrates toward the north. We visited 10 localities along the south coast of Nicaragua (San Juan del Sur, Rivas Department) and used a rapid assessment methodology (four 25-m long transects) to quantify the densities and diversity of coral, fishes, motile macroinvertebrates, and algae. A total of 52 fish, 11 echinoderm, 5 mollusk, 2 crustacean, 13 coral, and 39 macroalgae species were identified along the transects. The mean coral cover was 9.05% ± 1.91, with the highest cover toward the north at Guacalito and Punta Gigante (18.50% ± 8.68 and 16.75% ± 5.25, respectively). The corals Pavona gigantea Verrill, 1869 and Pocillopora spp. were the main reef-builders. The area between Guacalito and Punta Gigante had the highest abundances of fishes and motile macroinvertebrates and was the most diverse site sampled within the San Juan del Sur area. We propose management action to protect the diversity and uniqueness of this region.